Political and Cultural Islam: A Historical Phenomenon in Indonesia - Azis Arifin; Didin Saepudin (Buletin Al-Turas, 2021)
This article aimed to reveal the periodization of political  and cultural Islam in Indonesia from time to time. In its development, political and cultural Islam had become an entity that hadattracted the attention of academics in Indonesia. Both types of Islam have always been part of the history of this nation. Therefore, the periodization of the rounds needs to be disclosed in a neat and measurable manner. This research was qualitative using a historical approach, and the existing data were presented in a descriptive analytical manner. The primary data of the research covered the statutes and bylaw of Islamic parties, such as Partai Syarikat Islam Indonesia (PSII), Masyumi Party, Partai Persatuan Pembangunan (PPP), Partai Keadilan Sejahtera (PKS) and Partai Bulan Bintang (PBB), while the secondary data were documents of works of Indonesian authors, journals, and online news or articles. The results revealed that the periodization of Indonesian political and cultural Islam started from pre-independence to post-reformation. PSII, Masyumi Party, PPP, PKS and PBB respectively were examples of political Islam that were established in their era. Meanwhile, cultural Islam was patronized by Jam'iyyat al-Khair, Al-Irsyad, Muhammadiyah, Persis and Nahdlatul Ulama (NU). Both types and groups of the Islam basically had the same goal, namely to carry out Sharia. Therefore, for the political and cultural Islam, the power and sympathy of the people seemed to support the realization of this goal.